Sexual orientation, prejudice and segregation - Erik Plug; Dinand Webbink; Nicholas G. Martin (Institute for the Study of Labor (IZA), 2011)
This paper examines whether gay and lesbian workers sort into tolerant occupations. With information on sexual orientation, prejudice and occupational choice taken from Australian Twin Registers, we find that gays and lesbians shy away from prejudiced occupations. We show that our segregation results are largely driven by those gay and lesbian workers with disclosed identities, and robust to the inclusion of unobserved factors that are inherited and observed factors that strongly correlate with productive skills and vocational preferences. Our segregation estimates are generally large and consistent with prejudice based theories of employer and employee discrimination against gay and lesbian workers.
urn:nbn:de:101:1-20110621319
Keywords: J15; J24; J71; 330; sexual orientation; occupational choice; discrimination; segregation